Visible-Light-Induced Organocatalytic Borylation of Aryl Chlorides - Zhang, Li; Jiao, Lei (Journal of the American Chemical Society, 2019)
The preparation of arylboronates from unactivated aryl chlorides in a transition-metal-free manner is rather challenging. There are only few examples to achieve this goal by using ultraviolet irradiation. Based on the mechanistic understanding of the diboron/methoxide/pyridine reaction system, we achieved photoactivation of the in situ generated super electron donor and developed a visible-light-induced organocatalytic method for efficient borylation of unactivated aryl chlorides.